Synthesis and isolation of theaflavin from fresh tea leaves as bioactive ingredient of antioxidant supplements - Shabri, Shabri; Maulana, Hilman (Research Institute for Tea and Cinchona, 2017)
Theaflavin (TF) is a product of catechin oxidation that give contribution to golden yellow color, brightness, briskness of black tea and has a potential as natural antioxidant activity. TF has a higher superoxide radical capture rate than EGCG (Epigallocatechin gallate). The study was to synthesize TF components in the form of extracts that have high antioxidants. Materials used in this research is bud+3 leaves from RITC clone (GMB 7). The research were caried out used 15 liters of tea leaves pulp per treatment, fermentation using fermentor with 15 L/min, 20 L/min and 25 L/min airflow treatment, separation of TF from thearubigin (TR) used 2.5% NaHCO3, and isolation of TF from impurity compounds used silica gel column with ethyl acetate/hexane as eluent, and DPPH (1,1-diphenyl-2-picryl hydrazyl) for antioxidant activity. The result showed that TF synthesis of fresh tea leaf catechin at water-air rate of 25 liters/minute could produced TF extract and yield TF purity extract with 1.01% and 39.15% in dry weight respectively after isolation by silica gel column. Antioxidant activity by DPPH from TF extract showed the smallest value of EC50 is 12.16 mg/L at 150 mg dose and its activity increased with the addition of concentration of TF extract.